Ecological and genomic analyses of candidate phylum WPS‐2 bacteria in an unvegetated soil. (28th June 2020) - Sheremet, Andriy; Jones, Gareth M.; Jarett, Jessica; Bowers, Robert M.; Bedard, Isaac; Culham, Cassandra; Eloe‐Fadrosh, Emiley A.; Ivanova, Natalia; Malmstrom, Rex R.; Grasby, Stephen E.; Woyke, Tanja; Dunfield, Peter F.
Summary: Members of the bacterial candidate phylum WPS‐2 (or Eremiobacterota) are abundant in several dry, bare soil environments. In a bare soil deposited by an extinct iron–sulfur spring, we found that WPS‐2 comprised up to 24% of the bacterial community and up to 10 8 cells per g of soil based on 16S rRNA gene sequencing and quantification. A single genus‐level cluster ( Ca. Rubrimentiphilum) predominated in bare soils but was less abundant in adjacent forest. Nearly complete genomes of Ca. Rubrimentiphilum were recovered as single amplified genomes (SAGs) and metagenome‐assembled genomes (MAGs). Surprisingly, given the abundance of WPS‐2 in bare soils, the genomes did not indicate any capacity for autotrophy, phototrophy, or trace gas metabolism. Instead, they suggest a predominantly aerobic organoheterotrophic lifestyle, perhaps based on scavenging amino acids, nucleotides, and complex oligopeptides, along with lithotrophic capacity on thiosulfate. Network analyses of the entire community showed that some species of Chloroflexi, Actinobacteria, and candidate phylum AD3 (or Dormibacterota) co‐occurred with Ca. Rubrimentiphilum and may represent ecological or metabolic partners. We propose that Ca. Rubrimentiphilum act as efficient heterotrophic scavengers. Combined with previous studies, these data suggest that the phylum WPS‐2 includes bacteria with diverse metabolic capabilities.